Analysis of Mathematical Problem-Solving Ability Based on Self-Efficacy and Self-Confidence of Class VIII Junior High School Students - Aida Ar Rahmah; Slamet Soro (Universitas Negeri Makassar, 2022)
This study aims to describe students’ mathematical problem-solving ability of Junior High School in terms of students’ self-efficacy (SE) and self-confidence (SC). This typr of research is descriptive qualitative. This research was conducted in class VIII at one of Junior High Schools in Jakarta. Subjects in this research based on the result of questionnaire selected 3 students who had SE and SC from high, medium and low. The research’s instruments are SE and SC questionnaires, mathematical problem-solving ability tests, and interviews.The test and non-test instruments were validated by expert validators before being tested for validity and reliability. The data analysis techniques uses the Miles and Huberman model for data reduction, data presentation, and drawing conclusions. Triangulation techniques was used to test the validity of the research data. The results of this research indicate that students with high SE and SC had the best mathematical problem-solving abilities compared to students with medium to low SE and SC. Students with high SE and SC fulfill 4 indicators of problem-solving ability with maximum scores. Students with medium to low SE and SC only met 3 indicators of problem-solving ability.